Comparing Social Media Reactions to Early Game Songs and Final Boss Music in Single Player Adventure Games - Laato Samuli; Rauti Sampsa (United States, 2023)
Single player video games unite players through shared experiences, passion and knowledge about the game. We investigate the role of video game music in this setting. We analyse comments (n=1893) on 20 popular single player adventure game songs on social media sorted into four clusters based on the following two variables (1) age of the game; and (2) whether the song appears early on in the game or at the end. We discovered that there are more similarities in the types of comments and sentiments between early game songs across games than between songs from the same game. Early game songs had more comments related to nostalgia, sadness and "feeling of home" compared to late game songs. Comments on late game songs were more focused on players' experiences while playing. Overall, all 20 songs had overwhelmingly more comments on associations (both game and life related) than on the actual song itself.
Proceedings of the 55th Annual Hawaii International Conference on System Sciences